Über kartographische Darstellungen der Vegetation des Himalaya - Schweinfurth, Ulrich (ERDKUNDE, 1958)
While working on a thesis about the distribution of the vegetation in the Himalayas, the author paid special attention to previous cartographic efforts in this field, some of which are mentioned and discussed. The author came to the conclusion that no steady cumulative progress has been made which corresponds to the increasing knowledge of this part of the world. In particular, some good ideas, once conceived, seem to have been soon for gotten. False conceptions appear to be fairly deeply rooted and can only, it seems, be eradicated step by step. The author himself, in working on a map of the vegetation of the Himalayas on 1 :1 mill, (now published on 1 :2 mill.), adhered to the principle of leaving botanically unknown parts of the area concerned as blanks on the map. Thereby he thinks he has restricted himself to what can be stated conscientiously and furthermore to have given impetus to such study and research as will complete the scheme.